2021
DOI: 10.1186/s12941-021-00428-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of urine microbiota in patients with lower urinary tract symptoms

Abstract: Introduction Inflammation and infection are causative factors of benign prostatic hyperplasia (BPH). Urine is not sterile, and urine microbiota identified by DNA sequencing can play an important role in the development of BPH and can influence the severity of lower urinary tract symptoms (LUTS). Materials and methods We collected mid-stream voided urine samples from BPH patients and control participants and stored them in a freezer at − 80 °C. All … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…However, voided urine samples were used, and the results should therefore be interpreted with caution as microbial contamination may have occurred. Recently, Lee et al showed that some bacterial genera were present in MSU samples of the BPH group [ 49 ]. Some bacterial genera correlated with a high IPSS, as well as severe storage and voiding symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…However, voided urine samples were used, and the results should therefore be interpreted with caution as microbial contamination may have occurred. Recently, Lee et al showed that some bacterial genera were present in MSU samples of the BPH group [ 49 ]. Some bacterial genera correlated with a high IPSS, as well as severe storage and voiding symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The focus was on the characteristics of the antimicrobial effect of substances secreted by Lactobacillus on clinical strains of P. mirabilis with the indication of the factor with the highest activity. On the basis of many studies, we expected that natural microbiota of the urinary tract which include Lactobacillus strains would positively affect the condition of the urinary system and have an inhibitory effect on the development of P. mirabilis infections [ 21 , 22 , 23 ]. Dysbiosis of the natural microbiota of the urinary tract is related to the development of infections.…”
Section: Discussionmentioning
confidence: 99%
“…An investigation into the association between the microbiota and CP/CPPS paved the way to studying similar associations between the microbiota in BPH and male LUTS ( Table 2 ) 34 , 35 , 36 , 37 , 38 . A previous study published in 2013 demonstrated that aging affects the microbiota in male midstream voided urine and showed an interesting trend.…”
Section: Bph Male Lower Urinary Tract Symptoms (Luts) and The Microbiomementioning
confidence: 99%
“… Dysbiosis of urine microbiota may be related to the development of BPH and the severity of LUTS. 38 BPH, benign prostatic hyperplasia; IPSS, International Prostate Symptom Score; LUTS, lower urinary tract symptoms; PCa, prostate cancer. …”
Section: Bph Male Lower Urinary Tract Symptoms (Luts) and The Microbiomementioning
confidence: 99%